Implementation and practical problems of chaos-based cryptography revisited - Teh, Je Sen; Alawida, Moatsum; Sii, You Cheng (Journal of information security and applications, 2020)
Chaos-based cryptography, since its inception, has become a widely published subject. Despite the vast amount of contributions in the area, its applications in real-world scenarios are minimal as compared to conventional cryptography. Chaotic maps have been used in the design of cryptosystems because they depict desirable characteristics such as pseudorandomness, complexity, and sensitivity to parameter changes. Despite these characteristics being analogous to cryptographic requirements, the resulting chaos-based cryptosystems are usually difficult to analyze, inefficient, and have reproducibility issues. In this paper, we highlight some of the problems which deter the practical application of chaos-based cryptosystems. We show that recently published work in reputable journals still do not address these problems and remain only of academic interest. We also perform experiments to depict some of the implementation issues of digital chaos that need to be taken into consideration when designing chaos-based algorithms. We then discuss a number of possible solutions that can be explored to overcome these problems.